CEO Stress, Aging, and Death - Mark Borgschulte; Marius Guenzel; Canyao Liu; Ulrike Malmendier (Institute of Labor Economics (IZA), 2023)
We assess the long-term effects of managerial stress on aging and mortality. First, we show that exposure to industry distress shocks during the Great Recession produces visible signs of aging in CEOs. Applying neural-network based machine-learning techniques to pre- and post-distress pictures, we estimate an increase in so-called apparent age by one year. Second, using data on CEOs since the mid-1970s, we estimate a 1.1-year decrease in life expectancy after an industry distress shock, but a two-year increase when anti-takeover laws insulate CEOs from market discipline. The estimated health costs are significant, also relative to other known health risks.
Keywords: G34; I12; M12; 330; managerial stress; life expectancy; apparent-age estimation; job demands; industry distress; visual machine-learning; corporate governance